A distributed system architecture for speech recognition - Alleva, Fil; Bisiani, Roberto; Forin, S.; Lerner, Richard A. (IEEE International Conference on ICASSP '86 Acoustics, Speech, and Signal Processing, 1986)
This paper is an overview of the software environment (called AGORA) that is being developed at Carnegie-Mellon University to support the devlopment of connected, speaker independent, speech recognition systems. This includes the design, implemenentation, testing and fast (parallel) execution of speech recognition programs composed of a large number of independent algorithms. Systems described within AGORA can be executed on a number of different multiprocessor configurations.